Mental illness potrayal in media: A summative content analysis of malaysian newspapers - Razali Z.A.; SaAd R.A.; Suhaila Sanip (Universiti Malaysia Sarawak, 2024)
Stigmatization of mental illness is closely related with media representation. Newspaper is regarded as the main source of information for Malaysian public. However, the portrayal of mental illnesses in this form of media was never assessed. This study was conducted with the aims of evaluating how Bahasa Melayu newspapers reported mental illness issues and to quantify the frequency of negative depiction versus positive depiction of mental illness patient. Four daily Bahasa Melayu newspapers were examined page by page by the researchers during a five-week period, from July to August 2015. These newspapers were chosen based on their average daily circulation. The selected articles were coded according to coding frame developed by the authors. The data were then analyzed qualitatively using content analysis. A total of 46 articles were selected for analysis. The majority of tone used in the headlines of these articles was neutral and the majority of the tone used in the text was negative. The most common keyword in these articles was sakit mental. The findings were similar to what have been reported in other studies. In order to prevent further negative stigma on mental illness, several recommendations were discussed. 2018, Universiti Malaysia Sarawak. All rights reserved.